Adaptive Leadership in Higher Education: Organizational Communication and Institutional Sustainability: JEL Classification: I23, M12, M14, O33, L20 - Brandon Steve; Nurafni Surahman; Andi Batari Ghinaa Sarman; Rifky Wahyudi; M. Akbar Faiz Taufik; Novika Ayu Triany (Newinera Publisher, 2026)
This study examines the role of adaptive leadership in higher education and its relationship with organizational communication and institutional sustainability. A qualitative exploratory case study was conducted at STIE Ciputra Makassar, Indonesia. Data was collected through semi-structured interviews, non-participant observation, and document analysis, and analyzed using thematic analysis. The findings show that adaptive leadership enables institutions to respond effectively to external changes such as regulatory shifts, technological development, and increasing competition in higher education. Leadership adaptability is reflected in flexible decision-making, contextual problem solving, and continuous organizational adjustment. Organizational communication plays a central role in strengthening adaptive leadership through open communication, consistent information flow, and participatory coordination among leaders, lecturers, and staff. The study further reveals that institutional sustainability is shaped not only by financial performance but also by academic quality, institutional reputation, and stakeholder trust. Adaptive leadership contributes to sustainability by enhancing organizational adaptability, supporting human resource development, and promoting data-driven decision-making. The results indicate that adaptive leadership, organizational communication, and institutional sustainability are interrelated and form an adaptive organizational system. In conclusion, adaptive leadership supported by effective organizational communication is a key factor in ensuring the sustainability of higher education institutions. This study contributes to leadership theory in higher education and offers practical implications for strengthening institutional resilience and competitiveness.